ANALYZING CONSUMER ATTITUDE BETWEEN MALE AND FEMALE TO PURCHASE INTENTION COUNTERFEIT WAKAI SHOES - Raintung, Michael (Journal of Asean Studies on Maritime Issues, 2017)
This research aims to find out if there is significant difference in purchase intention based on social influence and value consciousness between male and female customers of counterfeit wakai shoes. Counterfeit products cause a considerable amount of damage in the free market economy. Moreover, future investment in research and development is placed at risk from the unfair competition generated by counterfeit products. The international trade of counterfeit product is enormous. Purchasing intention of counterfeit wakai shoes are currently increasing because there are a lot of people who become the buyers of this product. Counterfeit wakai shoes are easy to found because it is sold everywhere. This research conducted by a quantitative method and this research population is the buyers of wakai counterfeit shoes. By using an Independent Sample t-test, this research conducted a hypothesis is significant difference in social influence and value consciousness between male and female customers of counterfeit wakai shoes. Based on the result of this research, the data is normally distributed and homogenous. The result shows that there are no significant differences in purchase intention based on social influence and value consciousness between male and female customers of counterfeit wakai shoes. Findings suggest that original manufactures have to make a mark or hologram unable to imitate so there will be a significant differences between original and counterfeit.Keywords: Counterfeiting, gender, social influence, value consciousness